Human genome editing technologies in the center of current transhumanistic discourse on human enhancement (Annals of the University of Bucharest. Philosophy Series, 2025)
The article deals with certain challenges connected with the progress of human enhancement technologies, where genome editing technologies form part of them. Today, the idea of human enhancement is the subject of considerable debate among various streams of transhumanist thinkers. The author rejects pessimistic and dystopian views on human enhancement technologies that see these technologies as one of the main risks for modern civilization, and instead defends the opposite view. It is claimed that although such technologies continue to be relatively poorly defined, they do and will belong to the 'good side' of current (future) technological progress. Namely, in the context of pragmatic and moderate transhumanism, human enhancement is primarily viewed as a way of improving the quality of human and social life. The article mainly refers to human genetic enhancement, noting that the invention of CRISPR/Cas9 technology about 10 years ago paved the way for a revolution in gene research and gene therapy. Before the emergence of CRISPR/Cas9 technology, bioethical discussions had mostly concentrated on classical bioethical dilemmas (autonomy, privacy, etc.). Yet, the situation has changed radically in the last 3 years when the first practical misuses of CRISPR-Cas 9 technology (the He Jiankui affair) in germline genome editing were reported. Although the author agrees with views calling for more scientific and broader social control of germline genome editing, strong support is given for the claims made by moderate and pragmatic transhumanists that modern democratic societies must ensure that objective and unbiased assessments of the benefits/risks of all types of human enhancement technologies are retained.
Keywords: human enhancement; genome editing technology; bioethics; moral entrepreneurship; CRISPR-Cas 9 technology; He Jiankui affair